Pelatihan Jumputan sebagai Aktivitas Pencegahan Demensia pada Ibu PKK Pra-lansia di Kelurahan Mantrijeron - Rizki Nor Amelia; M Fikri Amrullah; Anggi Ristiyana Puspita Sari; Sri Rejeki Dwi Astuti; Hendra Hendra (Universitas Negeri Makassar, 2023)
Dementia is one of the scourges that must be faced in old age. Dementia prevention can start early, namely during the pre-elderly period. This service is carried out to help pre-elderly in the Kelurahan Mantrijeron prepare themselves to become healthy, independent, and productive elderly people through jumputan training with the tie and dip technique. The method used is descriptive qualitative with data collection techniques in the form of surveys, observations, and documentation. Data analysis was carried out descriptively both qualitatively and quantitatively to get a complete picture of the response from the participants to the training that had been carried out. In general, the results of the training evaluation show that the participants gave a positive response where all the indicators measured were in the very good category.